2021
DOI: 10.1002/cam4.3777
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA XIST/miR‐125b‐2‐3p axis modulates cell proliferation and chemotherapeutic sensitivity via targeting Wee1 in colorectal cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…For example, a high level of ENSG00000254615 was related to the repression of tumor growth and the inhibition of 5-FU resistance in CRC [23]. XIST enhanced the chemoresistance and tumorigenesis of CRC by adsorbing miR-125b-2-3p and elevating WEE1 [24]. Previous studies reported that SNHG11 acted as a contributor in triple-negative breast cancer [25], hepatocellular carcinoma [26] and pancreatic carcinoma [27] through different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a high level of ENSG00000254615 was related to the repression of tumor growth and the inhibition of 5-FU resistance in CRC [23]. XIST enhanced the chemoresistance and tumorigenesis of CRC by adsorbing miR-125b-2-3p and elevating WEE1 [24]. Previous studies reported that SNHG11 acted as a contributor in triple-negative breast cancer [25], hepatocellular carcinoma [26] and pancreatic carcinoma [27] through different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to our study, the expression of miR-125b-2-3p was rather decreased in other types of cancer. In colorectal cancer, tissue and cell line expression of this miR was decreased, and overexpression increased sensitivity to drugs [ 65 ]. In a similar way, miR-125b-2-3p was significantly lower in HCC than in non-tumor tissue [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…133 In addition, XIST can activate the Wnt/β-catenin signaling pathway to accelerate bladder and colon cancer progression by sponging miR-139-5p 105 and miR-34a 109 respectively. XIST targets miR-200b-3p to modulate the expression of ZEB1 , 134 sponges miR-132-3p to activate the MAPK1 signaling pathway, 110 interacts with miR-137 to regulate the EZH2 signaling pathway, 117 binds miR-486-5p to regulate the neuropilin-2 (NRP-2) pathway, 108 inhibits miR-30a-5p to activate ROR1, 135 suppresses miR-93-5p to modulate the HIF-1A/AXL signaling pathway, 136 sponges miR-338-3p to regulate PAX5 expression, 137 and targets miR-125b-2-3p to regulate the Wee1 signaling pathway, 138 all of which promote colorectal cancer progression. XIST can also promote TGF-β-induced epithelial–mesenchymal transition through the miR-367/141-ZEB2 120 and miR-137/Notch-1 124 axes in non-small cell lung cancer.…”
Section: Xist and Sex-biased Diseasesmentioning
confidence: 99%